Site-selective Suzuki–Miyaura coupling of heteroaryl halides – understanding the trends for pharmaceutically important classes. Issue 1 (2nd September 2016) - Almond-Thynne, Joshua; Blakemore, David C.; Pryde, David C.; Spivey, Alan C.
Abstract : Suzuki–Miyaura cross-coupling reactions of heteroaryl polyhalides with aryl boronates are surveyed. Drawing on data from literature sources and Pfizer's global chemistry RKB and CAS Scifinder® databases, factors that determine the site-selectivity of these reactions are discussed with a view to rationalising the trends. Abstract : Suzuki–Miyaura cross-coupling reactions of heteroaryl polyhalides with aryl boronates are surveyed. Drawing on data from literature sources as well as bespoke searches of Pfizer's global chemistry RKB and CAS Scifinder® databases, the factors that determine the site-selectivity of these reactions are discussed with a view to rationalising the trends found.